Pengaruh Edukasi Terhadap Pengetahuan Dan Sikap Tentang Keputihan Patologis Di SMAN 2 Luwu Timur (Window of Public Health Journal, 2025)
Vaginal discharge (white discharge, leukorrhea, fluor albus) is a non-bloody vaginal discharge. Pathological vaginal discharge is a high-risk condition for young women aged 15-24 years, making it a common reproductive health problem. Initial observations at State Senior High School 2, East Luwu, showed that most female students lacked knowledge about pathological vaginal discharge and tended to consider it normal without seeking treatment. This situation is exacerbated by the limited reproductive health education received in the school environment. The purpose of this study was to determine the effect of health education on knowledge and attitudes about preventing pathological vaginal discharge in young women at State Senior High School 2, East Luwu. This study used a pre-experimental research design with a one-group pre-post-test approach. Data collection was conducted in July 2024. The sample size was 245 subjects. Sampling was carried out using a purposive sampling technique. Data processing was performed using the Wilcoxon test (p